The impact of ethical implications intertwined with tuberculosis household contact investigation: A qualitative study - Lebohang M. Mlambo; Minja Milovanovic; Colleen F. Hanrahan; Kegaugetswe Motsomi; Mashido T. Morolo; Mbali M. Mohlamonyane; Nicholas W. Albaugh; Khatija Ahmed; Neil Martinson; David W. Dowdy; Nora S. West (PLoS ONE, 2026)
Background Household contact investigation (HCI) is an effective and widely used approach to identify persons with tuberculosis (TB) disease and infection globally. Despite widespread recommendations for the use of HCI, there remains poor understanding of the impact on and value of contact investigation for participants. Further, how HCI as a practice impacts psychosocial factors, including stigma and possible unintended disclosure of illness among persons with TB, their families, and communities, is largely unknown. Methods This exploratory qualitative study nested within a randomized trial (ClinicalTrials.gov: NCT04520113, 17 August 2020) was conducted in South Africa to understand the impacts of HCI on index patients living with TB and their household contact persons in two rural districts in the Limpopo province (Vhembe and Capricorn) and Soshanguve, a peri-urban township in Gauteng province. People with TB and household members of people with TB were recruited to participate in in-depth interviews and focus group discussions using semi-structured guides. We explored individual, interpersonal, and community-level perceptions of potential impacts of household contact investigation to elucidate their perceptions of HCI. Thematic analysis identified key themes. Results Twenty-four individual interviews and six focus group discussions (n = 39 participants) were conducted. Participants viewed HCI as an effective approach to finding TB cases, helpful in educating households about TB symptoms and reducing barriers to health-related services. At the interpersonal level, HCI aided people with TB in safely disclosing their TB status to family members and facilitated family and social support for accountability. The introduction of HIV testing during HCI was reported by some participants as making household members slightly uncomfortable, decreasing interest in household members being tested for TB. HCI negatively impacted community-level TB and HIV-related stigma due to healthcare worker visibility at home. Conclusion Our data suggests varying impacts of HCI on people with TB, their families and interpersonal relationships, and communities, highlighting the importance of considering approaches that address concerns about community stigma and HIV testing to enhance acceptance of HCI. Trial registration ClinicalTrials.gov NCT 04520113